Better public transit systems : analyzing investments and performance - Bruun, Eric Christian (Abingdon, Oxon ; New York, NY : Routledge, 2014)
"Better Public Transit Systems is a complete primer for performance and investment analysis of public transportation. Whether you're planning a major new public transit project, an extension or expansion of an existing system, or simply evaluating the needs of your current system, this book provides the tools you need to define your goals and objectives and conceive and analyse design alternatives. This completely revised Second Edition includes new material for students, with questions at the end of each chapter, whilst remaining a useful reference book"--Provided by publisher.
1. The Premise and Contents of the Second Edition -- 2. Establishing Goals and Objectives -- 3. Route and Network Analysis -- 4. The Impact of Intelligent Transportation Systems (ITS) -- 5. Characterizing and Influencing Modal Relationships -- 6. Space Requirements and Impacts from Land Use -- 7. Simple and Complex Mathematical Models -- 8. Methods to Evaluate a Transit Project in Monetary Terms -- 9. Cost Model Development -- 10. Average and Marginal Costs of Services -- 11. Organizational Structures and Contract Models -- 12. Simultaneous Evaluations of All Factors.
Includes bibliographical references and index.
Keywords: Transportation; Urban transportation; Local transit